Evaluation of Vitamin D isolated or Associated with Teriparatide in Peri-Implant Bone Repair in Tibia of Orchiectomized Rats - Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Frigério, Paula Buzo [UNESP]; de Moura, Juliana [UNESP]; Duarte, Nathália Dantas [UNESP]; de Oliveira, Danila [UNESP]; Deering, Joseph; Grandfield, Kathryn; Okamoto, Roberta [UNESP] (MDPI, 2023)
(1) Background: The objective of this study was to evaluate the morphometry of peri-implant bone tissue in orchiectomized rats, treated with vitamin D isolated or associated with teriparatide. (2) Methods: 24 rats were divided into 4 groups: ORQ—orchiectomy, without drug treatment, ORQ+D—orchiectomy, treated with vitamin D, ORQTERI—orchiectomy, treated with teriparatide and ORQTERI+D—orchiectomy, treated with teriparatide + vitamin D. Each animal received an implant in the tibial metaphysis. Euthanasia occurred 60 days after implant surgery. Computed microtomography (micro-CT) was performed to evaluate the parameters of volume and percentage of bone volume (BV, BV/TV), trabecular thickness (Tb.Th), number and separation of trabeculae (Tb.N, Tb.Sp) and percentage of total porosity (Po-tot). Data were subjected to 1-way ANOVA and Tukey post-test, with a significance level of 5%. (3) Results: For the parameters BV, BV/TV, Tb.Th, the ORQTERI+D group showed the highest values in relation to the other groups and for Po-tot, the lowest values were for ORQTERI+D. For Tb.Sp and Tb.N, there was no statistically significant difference when comparing intragroup results (p > 0.05). (4) Conclusions: It was possible to conclude that treatment with vitamin D associated with teriparatide increases bone volume and improves bone quality.
Keywords: dental implants; men; osteoporosis; teriparatide; vitamin D